Investing in our education leading, learning, researching and the doctorate - Rayner, Stephen; Taysum, Alison (International perspectives on higher education research ;, 2014)
This volume acknowledges the need for better understanding in leadership, management and administration of new knowledge which is crucial for effective leadership in a period of massive policy reform and deepening austerity in education. The doctorate is key to meeting this global challenge as it offers new and valid ways of enabling innovation and utility in an approach to knowledge creation and management that embodies meaningful methods for assuring improvement, effectiveness, efficiency and equity in education. The chapters in this edited collection emerge from a British Educational Leadership Management and Administration Society (BELMAS) funded Seminar Series. The international leading academics and researching practitioners contributing chapters to the book focus upon purposes, pedagogies and the impact of the doctorate on educational leaders and leadership development. Further, the chapters reveal how doctoral study helps equip leaders to implement policy and develop strategies to steer their organizations towards improving policy provision, and practice.